Addiction Debates : hot topics from policy to practice - Comiskey, Catherine (Thousand Oaks : SAGE Publishing, 2019)
"The proposed book will explore the current tumultuous landscape of addiction research, policy and practice. Covering all the 'hot topics' of the day in a balanced and informative manner, the book will aim to provide an international perspective on each of the challenges, present the prevailing evidence and stimulate discussion and development of these arguments for further research and debate. Covering debates from the legalisation of cannabis, to the opioid epidemic and whether governments should aim for harm reduction, rehabilitation or abstinence, this text will look at different approaches taken globally, from safe injecting facilities, to punitive measures and the effectiveness of each. It will also look into the health and social concerns related to drug consumption, such as the effect on family members of drug takers, particularly children, and the impact on users' health and the pressure that puts on health and associated services. Taking an international approach with case studies and research from countries including the US, Canada, Portugal, Australia and the Philippines, this text will be relevant to readers from a range of disciplines including: counselling and psychotherapy; psychiatry; applied psychology; nursing; social work; public and global health, and I think it will make a valuable addition to the swift series"--